Liturghia, text esențial în formarea caracterului moral și spiritual al culturii române - Ana Bobu (Revista de Istorie și Teorie Literară)
For the Liturgy of St. John Chrysostom, we have established its place within the Romanian culture by summarizing the history of the liturgical text on two levels: on the ethical one and on the cultural ages level; by the methods of observation and deduction, we have set its typology and we have presented the coordinates of all the liturgical manuscripts and printed books, we established its typology and we presented the cultural dimension of the book manuscripts, which revealed aspects of social and cultural history of Romanians.